On multidecadal and quasi-decadal North Atlantic variability - Alvarez-Garcia, F.; Latif, Mojib; Biastoch, Arne (Journal of Climate, 2008)
Observed sea surface temperatures (SSTs) in the North Atlantic from 1958 through 2000, as well as data from an ocean model simulation driven with the atmospheric variability observed during the same period, are examined using multichannel singular spectrum analysis. The two leading oscillatory modes are associated with a multidecadal and a quasi-decadal period. The former is connected to a basinwide uniform SST pattern and changes in the deep North Atlantic meridional overturning circulation. The quasi-decadal mode involves a tripolar SST anomaly pattern forced by atmospheric variability with a spatial structure resembling that of the North Atlantic Oscillation (NAO). The upper ocean’s dynamical response to this NAO variability provides an instantaneous positive feedback to the SST pattern, while a delayed negative feedback is due to shallow overturning circulation anomalies.